2021
DOI: 10.15414/afz.2021.24.02.124-128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cashew (Anacardium occidentale) nut shell stored and fresh extracts on cowpea bruchid, Callosobruchus maculatus (Fabricius.) (Coleoptera: Chrysomelidae)

Abstract: Licensed under a Creative Commons Attribution 4.0 International License A laboratory study was carried out to evaluate the efficacy of cashew nut shell extract in the control of cowpea bruchid, Callosobruchus maculatus (Fab.) under prevailing laboratory conditions. Fresh ethanolic and stored extract of cashew nut shell served as treatments which were compared with untreated control. Data collected on adult mortality, total number of emerged progeny (adults), number and weight of damaged seeds (seeds with holes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Likewise, the trial of 17.5 g carbaryl also performed a significant sign with less ant population than the concentration of 1% of CNSL and the control. The CNSL extract affects the controlling activities of insects an effect that had been reported by many authors such as Callosobruchus maculatus 23 , 3rd-stage of Aedes aegypti larvae 21 and 3rd-stage and 4th-stage of A. aegypti larvae 16 . The scoring average of ant population density was about 2.25 but it seemed to have a much higher than trials of 10 and 20% concentration.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Likewise, the trial of 17.5 g carbaryl also performed a significant sign with less ant population than the concentration of 1% of CNSL and the control. The CNSL extract affects the controlling activities of insects an effect that had been reported by many authors such as Callosobruchus maculatus 23 , 3rd-stage of Aedes aegypti larvae 21 and 3rd-stage and 4th-stage of A. aegypti larvae 16 . The scoring average of ant population density was about 2.25 but it seemed to have a much higher than trials of 10 and 20% concentration.…”
Section: Discussionmentioning
confidence: 60%
“…Not just insect repellent role, antibacterial and antifungal are other roles of the substances of CNSL since it consists of anacardate acid aiming to break the pathway of Prostaglandin synthetase 18 . This enzyme has a vital role in prostaglandin development to support the physiological and reproductive systems of insects 23 .…”
Section: Discussionmentioning
confidence: 99%
“…(Brassicales: Moringaceae), due to their nutritional and medicinal properties (Baptista et al, 2018;Gandji et al, 2018) [6,13] . These plants have exhibited considerable potentials in effectively managing pests, specifically those affecting stored products (Buxton et al, 2017;Babatunde et al, 2021) [7,5] . For instance, laboratory and field studies have demonstrated the efficacy of aqueous moringa extracts in controlling pests of cabbage and watermelon (Alao et al, 2018;Ogbonna et al, 2021) [2,18] .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, extracts from A. occidentale, such as cashew nut shell liquid, cashew seed powder, and extracts of cashew leaves, have been identified as valuable alternatives to synthetic pesticides. These extracts have proven effective in reducing the population of pests like Callosobruchus maculatus, C. sibinnotatus, and Sitophilus oryzae and inhibiting the emergence of larvae of pests such as Anticarsia gemmatalis and Spodoptera frugiperda (de Carvalho et al, 2019; Babatunde et al, 2021) [9,5] . Moringa and cashew extracts are particularly beneficial as they pose no harm to humans, the environment, and beneficial arthropods like parasitoids, pollinators, and predators.…”
Section: Introductionmentioning
confidence: 99%